Sosialisasi Public Speaking dan Penggunaan Canva untuk Presentasi pada Siswa SDIT Al Fatih Depok - Nova Shafira Sunarto Putri; Nada Shofiyah; Bintang Ramasalsa Indrabudi; Sakal Tua Muda Nababan; Yani Hendrayani (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
The socialization activity on public speaking and Canva presentation design, conducted by postgraduate students of Communication Science at UPN “Veteran” Jakarta, was held at SDIT Al Fatih Depok and aimed at equipping third-grade students with essential communication skills in the Society 5.0 era. This initiative represents a concrete form of community engagement, particularly in strengthening basic education that is responsive to technological advancement and modern educational demands. Students were introduced to fundamental public speaking techniques, including voice modulation, articulation, expressive gestures, and basic voice-over practices to enhance their vocal delivery. Furthermore, Canva was introduced as a visual aid tool, enabling students to design engaging and comprehensible presentations. Although most participants had never used Canva before, their eagerness to learn and adapt was evident. Evaluation results indicated a notable improvement in students’ self-confidence when speaking publicly, alongside enhanced creativity in visualizing their ideas. This program not only developed verbal and visual communication skills but also laid a foundation for digital and media literacy from an early age. Ultimately, the activity aspires to nurture a generation that is communicative, confident, and technologically competent in facing future global challenges.